Should we abstain from treating women with endometriosis using menopausal hormone therapy, for fear of an increased ovarian cancer risk?. (August 2015) - Rozenberg, S.; Antoine, C.; Vandromme, J.; Fastrez, M.
Abstract Women suffering from endometriosis often have an early menopause, resulting in severe menopausal symptoms and an increased risk of osteoporosis. They are therefore candidates for menopausal hormone therapy (MHT). Unfortunately, MHT may increase the risk of endometriosis recurrence. Moreover, endometriosis patients are at increased risk of ovarian cancer, which may be further enhanced by MHT use. It is unknown, however, whether MHT more frequently increases type I (low-grade serous tumors), which seem to be increased when endometriosis is present, or type II (the more aggressive high-grade serous) tumors. We propose the following decision-making algorithm for endometriosis patients considering MHT. Those who have been treated with bilateral salpingo-oophorectomy, and in whom there is no residual endometriotic disease, can probably be treated using MHT without risk of endometriosis recurrence or fear of ovarian cancer. For women with significant, residual endometriosis lesions, the benefit may outweigh the risks, when menopause is reached before the age of 45 years or when severe symptoms are present.